Trends and Advances in Information Systems and Technologies Volume 1 - Rocha, Álvaro; Adeli, Hojjat; Reis, Luís Paulo; Costanzo, Sandra; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book includes a selection of papers from the 2018 World Conference on Information Systems and Technologies (WorldCIST'18), held in Naples, Italy on March27-29, 2018. WorldCIST is a global forum for researchers and practitioners to present and discuss recent results and innovations, current trends, professional experiences and the challenges of modern information systems and technologies research together with their technological development and applications. The main topics covered are: A) Information and Knowledge Management; B) Organizational Models and Information Systems; C) Software and Systems Modeling; D) Software Systems, Architectures, Applications and Tools; E) Multimedia Systems and Applications; F) Computer Networks, Mobility and Pervasive Systems; G) Intelligent and Decision Support Systems; H) Big Data Analytics and Applications; I) Human-Computer Interaction; J) Ethics, Computers & Security; K) Health Informatics; L) Information Technologies in Education; M) Information Technologies in Radiocommunications; N) Technologies for Biomedical Applications.
Mexican Spanish Affective Dictionary -- Legal and economic aspects of virtual organizations -- Improving Employee Recruitment through Data Mining -- Facial Emotion Detection in Massive Open Online Courses -- Towards information warehousing: A case study for tweets -- Implementation of Paperless Office in The Classroom -- Search in collections of mathematical articles -- A P2P algorithm for a smart information system -- Learning ecosystem metamodel quality assurance.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence